Mode‐stirred reverberating chamber Doppler spectra: multi‐frequency measurements and empirical model. Issue 15 (1st December 2014) - Sorrentino, Antonio; Gifuni, Angelo; Ferrara, Giuseppe; Migliaccio, Maurizio
Abstract : A new empirical model for the Doppler spectrum of the received field obtained in a reverberating chamber (RC) when the continuous mechanical stirring is employed, is proposed. The characterisation of the Doppler spectrum is 2‐fold: on the one side, it allows synthesising an electromagnetic field with desired characteristics within the chamber; on the other side, if the RC is used as a wireless emulator, any wireless propagation environments can be properly emulated within the chamber. The model is successfully tested on an extensive set of measurements accomplished at the RC of the Università degli Studi di Napoli Parthenope, formerly Istituto Universitario Navale (IUN). Results, confirm the effectiveness of the prosed method.